In Vitro Inhibition of Helicobacter pylori Growth by Redox Cycling Phenylaminojuglones. (24th April 2018) - Benites, Julio; Toledo, Héctor; Salas, Felipe; Guerrero, Angélica; Rios, David; Valderrama, Jaime A.; Calderon, Pedro Buc
Abstract : Infection by Helicobacter pylori increases 10 times the risk of developing gastric cancer. Juglone, a natural occurring 1, 4-naphthoquinone, prevents H. pylori growth by interfering with some of its critical metabolic pathways. Here, we report the design, synthesis, and in vitro evaluation of a series of juglone derivatives, namely, 2/3-phenylaminojuglones, as potential H. pylori growth inhibitors. Results show that 5 out of 12 phenylaminojuglones (at 1.5 μ g/mL) were 1.5–2.2-fold more active than juglone. Interestingly, most of the phenylaminojuglones (10 out of 12) were 1.1–2.8 fold more active than metronidazole, a known H. pylori growth inhibitor. The most active compound, namely, 2-((3, 4, 5-trimethoxyphenyl)amino)-5-hydroxynaphthalene-1, 4-dione 7, showed significant higher halo of growth inhibitions (HGI = 32.25 mm) to that of juglone and metronidazole (HGI = 14.50 and 11.67 mm). Structural activity relationships of the series suggest that the nature and location of the nitrogen substituents in the juglone scaffold, likely due in part to their redox potential, may influence the antibacterial activity of the series.